Rare anemias in adolescents - Vives-Corrons, Joan Lluis; Krishnevskaya, Elena (Acta Biomedica Atenei Parmensis, 2021)
ABSTRACT Anemia can be the consequence of a single disease or an expression of external factors mainly nutritional deficiencies. Genetic issues are important in the primary care of adolescents because a genetic diagnosis may not be made until adolescence when the teenager presents with the first signs or symptoms of the condition. This situation is relatively frequent for rare anemias (RA) an important, and relatively heterogeneous group of rare diseases (RD) where anemia is the first and most relevant clinical manifestation of the disease. RA are characterized by their low prevalence (< 1 per 10,000 individuals), and, in some cases, by their complex mechanism. For these reasons, RA are little known, even among health professionals, and patients tend to remain undiagnosed or misdiagnosed for long periods of time, making it impossible to know the prognosis of the disease or to carry out genetic counseling for future pregnancies. Since this situation is an important cause of anxiety for both adolescent patients and their families, the physician’s knowledge of the natural history of a genetic disease will be the key factor for the anticipatory guidance for diagnosis and clinical follow-up. RA can be due to three primary causes: 1.Bone marrow erythropoietic defects, 2. Excessive destruction of mature red blood cells (hemolysis), and 3. Blood loss (bleeding). More than 80% of RAs are hereditary, and about 20% remain undiagnosed but when their first clinical manifestations appear during childhood or adolescence, they are frequently misdiagnosed with iron deficiency. For this reason, RA are today an important clinical and social health problem worldwide